THE EFFECT OF FEEDING FREQUENCY ON THE GROWTH AND SURVIVAL RATE OF MUD CRAB(Scylla serrata) - Rizal B Lumban Gaol; Usman M Tang; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT             Mudcrabs (Scylla serrata) are one of the fisheries commodities that have high economic value. Feed is the most important production factor in the cultivati of mud crabs. To determine the effect of appropriate feeding frequency and find out the best frequency for the growth and survival of mudcrabs (Scylla serrata). The method used in this study was to use a Completely Randomized Design (CRD) with a frequency of 5 feeding factors, namely 1, 2, 3, 4 and 5 times a day. Treatment 1 (Feeding once a day), Treatment 2 (Feeding 2 times a day), Treatment 3 (Feeding 3 times a day), Treatment 4 (Feeding 4 times a day), Treatment 5 (Feeding 5 times a day). thus 15 units of experimental containers are needed with a container area of 59 x 37 x 17 cm3. Parameters observed included absolute weight growth, daily growth rate, feed efficiency, feed conversion, survival and quality water. The results showed that the frequency of feeding 3 times a day was the best treatment with absolute weight of 74 cm, absolute length of 2.10 cm, specific growth rate, 1.37%, feed efficiency 89.89%, feed conversion 1.11% , Survival rate 91.6%. Based on the results of the study the frequency of feeding 3 times a day is good to be applied to the growth of Mudcrabs (Scylla serrata).Keywords: Mullet Fish, Mudcrab, Absolute Weight Growth, Daily Growth Rate, Feed Efficiency, Feed Conversion, Survival